Rodzinne uwarunkowania problemów i zaburzeń psychicznych u dzieci i młodzieży = Family conditions of problems and mental disorders in children and adole scents - Grzegorzewska, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The prevalence rate of children and adolescents affected by anxiety, attention deficit, depression, addictions and other disorders is conservatively estimated at 10-20% young people at any given time. The needs of children with psychological dysfunction are complex. In order to provide children with quality care and appropriate management of mental health problems, it is important to understand some of the contextual issues (means family factors) that underlie a child's etiology of a mental disorder.
Keywords: zdrowie psychiczne; dzieci i młodzież; przywiązanie; struktura rodziny; mental health; children and adolescents; attachment; structure of family